ISLAM IN INDONESIA A STUDY OF VISUAL AND VIRTUAL MUSLIM IDENTITY FORMATION - Syofrianisda; Yondrizal; Dasrizal Dahlan; Desi Asmaret (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
ABSTRACT Islam is the majority religion in Indonesia and plays a central role in shaping the country's social, cultural and political landscape. With more than 230 million adherents or about 87% of the total population, Indonesia has the largest Muslim community in the world. This phenomenon is often identified through the term Islam Nusantara, which describes a distinctly Indonesian form of Islam. The concept emphasizes harmony, mutual cooperation and tolerance, while adhering to the core teachings of Islam. This article aims to discuss the dynamics of thought between two groups of Muslims in Indonesia: visual Muslims (traditional) and virtual Muslims (modern). The study explores how these two groups understand Islam Nusantara and construct their identities. The research approach is conducted through a structured literature study and includes important methodological steps to achieve the objectives of the analysis. The research reveals significant differences between the two groups. Visual (traditional) Muslims are more inclined towards preserving local traditions as the core of religious practice, while virtual (modern) Muslims tend to accept global influences and focus on innovation and renewal in understanding religion.